2012
DOI: 10.1371/journal.pone.0049504
|View full text |Cite
|
Sign up to set email alerts
|

Signal Molecules Mediate the Impact of the Earthworm Aporrectodea caliginosa on Growth, Development and Defence of the Plant Arabidopsis thaliana

Abstract: Earthworms have generally a positive impact on plant growth, which is often attributed to a trophic mechanism: namely, earthworms increase the release of mineral nutrients from soil litter and organic matter. An alternative hypothesis has been proposed since the discovery of a signal molecule (Indole Acetic Acid) in earthworm faeces. In this study, we used methodologies developed in plant science to gain information on ecological mechanisms involved in plant-earthworm interaction, by looking at plant response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(31 citation statements)
references
References 49 publications
0
29
0
2
Order By: Relevance
“…Puga-Freitas et al (2012) proposed that signal molecules (such as indole acetic acid, IAA) may mediate the earthworm effects on plant growth. They also showed that earthworms change the expression of genes responsive to abiotic and biotic stress, and to the application of exogenous hormones.…”
Section: Mechanisms Of How Detritivores Affect Plant and Aboveground mentioning
confidence: 99%
“…Puga-Freitas et al (2012) proposed that signal molecules (such as indole acetic acid, IAA) may mediate the earthworm effects on plant growth. They also showed that earthworms change the expression of genes responsive to abiotic and biotic stress, and to the application of exogenous hormones.…”
Section: Mechanisms Of How Detritivores Affect Plant and Aboveground mentioning
confidence: 99%
“…fragariae (related to fruit production) following the earthworm inoculation in this experiment was not expected, as normally the positive effects of these invertebrates in the soil negate the negative consequences of plants pathogens (DEMETRIO et al, 2017;LAFONT et Several surveys have reported positive effects of earthworms on plant growth (LAOSSI et al, 2010;PASHANASI et al, 1996;PUGA-FREITAS et al, 2012). This effect can occur in different ways, with increased available nitrogen probably the main factor in this phenomenon, due to the high uptake by the plants and typical low availability in the soil (AGREN et al, 2012).…”
Section: Resultsmentioning
confidence: 76%
“…The observed increases in T1 in relation to control represent around 1,000 kg per hectare (considering 24,000 strawberry plants hectare -1 ). (LAOSSI et al, 2010;PASHANASI et al, 1996;PUGA-FREITAS et al, 2012). This effect can occur in different ways, with increased available nitrogen probably the main factor in this phenomenon, due to the high uptake by the plants and typical low availability in the soil (AGREN et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Earthworms are known to modify the expression of genes involved in autolysis, enabling the plant to mobilize nutrients an energy rapidly in response to stress, and that of genes involved in the biosynthesis pathway of jasmonic acid, a plant hormone controlling defense mechanisms (Blouin et al, 2005). Indole acetic acid, from the auxin family, also seems to be involved in the effect of earthworms on plants: the dwarf phenotype of an auxin-transport mutant of Arabidopsis thaliana can be converted to the wild-type phenotype in the presence of earthworms (Puga-Freitas et al, 2012b) with IAA-containing casts (Muscolo et al, 1998;Quaggiotti et al, 2004). Far from being an exception, this modification of plant immunity and development through signal molecules appears to be a common feature of soil organisms, from microorganisms, to the micro-, meso-and macro-fauna (Puga-Freitas and .…”
Section: Consequences For Plant Growth Soil Nutrient Availability Amentioning
confidence: 99%
“…We hypothesized that these effects might also result in a lower incidence of eyespot in the presence of earthworms. The mechanisms underlying this control of parasite incidence in the presence of earthworms may involve indirect effects due to improvements in the nutritional status of the plant in the presence of earthworms (Whalen and Parmelee, 2000) or direct effects on plant defense mechanisms and the induction of induced systemic resistance (Puga-Freitas et al, 2012b;Puga-Freitas and Blouin, 2015).…”
Section: Introductionmentioning
confidence: 99%